POLITICAL PARTY’S CRIMINAL LIABILITY IN INDONESIA - Mulyati, Nani; Santoso, Topo (UI Scholars Hub, 2019)
In Indonesia, according to civil law, a political party can be a separate legal personality from its members vested with the same legal rights and duties as a legal citizen. They can participate in the economic, politic, legal, and social relationships. If they violate the law, they can also be held responsible. However, it is still very doubtful whether they can be liable in criminal law since they have critical function in the democratic political process as acknowledge by the constitution. This paper examines the position of a political party in their criminal liability, whether they can be prosecuted, and sanctioned. In order to do that the scientific methodology used for this research is doctrinal legal research, scrutinizing some theories, regulations, and legal cases, and analyzing some legal theories on corporate legal personalities. It examines regulations and cases that describe the conditions when a political party can or cannot be prosecuted as political parties. It is concluded that political parties do have some peculiarities that ordinary private corporations do not, such as the important roles they play in constitutional life as they can contest election results and hold power in the government. Some countries treat political parties differently when it comes to criminal law. This research will provide valuable information for judges, other law enforcement officers, and academia in understanding the position of political parties in criminal liability.